2016
DOI: 10.1038/ejcn.2016.151
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate extract alleviates disease activity and some blood biomarkers of inflammation and oxidative stress in Rheumatoid Arthritis patients

Abstract: POMx alleviates disease activity and improves some blood biomarkers of inflammation and oxidative stress in RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(75 citation statements)
references
References 50 publications
1
73
0
1
Order By: Relevance
“…It has been suggested that the inhibitory effects of EA are greater than GA and PU on nitrite production (BenSaad et al, ). Moreover, EA protected the DNA double helix against different alkylating agents (Ghavipour et al, ; Khodadadi & Nasri, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the inhibitory effects of EA are greater than GA and PU on nitrite production (BenSaad et al, ). Moreover, EA protected the DNA double helix against different alkylating agents (Ghavipour et al, ; Khodadadi & Nasri, ).…”
Section: Resultsmentioning
confidence: 99%
“…POMx significantly reduced the score of DAS28 as an indicator of reducing tender joints, pain intensity, swelling, and erythrocyte sedimentation rate (ESR) levels after 8 weeks. Moreover, POMx meaningfully diminished the morning stiffness and HAQ score, while enhanced the level of GPx content and activity (Ghavipour et al, ). In another study, eight patients with active RA received pomegranate extract (10 mL daily) for 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism for the protective effect of tea on RA is still unclear. RA is a chronic inflammatory disease of the joints with systemic overproduction of pro-inflammatory cytokines such as IL-6 and TNF-α [21]. Tea contains EGCG, a potent anti-inflammatory molecule found in green, oolong and black tea that affects IL-6 activity and trans-signalling [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate (2 capsules of 250 mg pomegranate extract/day for 8 weeks) improved disease activity, some inflammatory blood biomarkers and oxidative stress (increased glutathione peroxidise) in 30 rheumatoid arthritis patients in a double-blind, placebo-controlled, randomized study [24].…”
Section: Clinical Studiesmentioning
confidence: 99%